(3RjL GdTSJcIs - (3MSjf Hf ehSi GdgQeRj GdMGSHs
(3ChdgG (B:s
(3gPG cJGH dWja jYQa HRjL GdTSJcI , Cdag GdMSjf Hf eShi GdgQeRi GdMGSH , deYQaI GdchGcH GdSHYI hGdLhRgQ hGdSGYGJ hGdCQJaGYGJ hGdELJeGYGJ hGdESJbHGdGJ hGdcShaGJ , heG jJYdb HC(B'(3eGd GdJbhje s
(3BNQgG (B:s
(3hLedI gPg GdCYeGd Ydi GdJbQjH , hGdMbjbI ai GdCYeGd HGdRjL ced GdcJGH HMeO Gddg s
(3fSNI KGfjIs
(3jJab ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa ai HYV GdCdaGX hGdYHGQGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B866 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3edi edc (B_ (3WgQGf (B(640) s
Keywords: (3Gdadcs